Long-term airborne dioxin exposure and breast cancer risk in a case-control study nested within the French E3N prospective cohort - Aurélie Marcelle Nicole Danjou; Thomas Coudon; Delphine Praud; Emilie Lévêque; Elodie Faure; Pietro Salizzoni; Muriel Le Romancer; Gianluca Severi; Francesca Romana Mancini; Karen Leffondré; Laure Dossus; Béatrice Fervers (Environment International, 2019)
Background: Dioxins, Group 1 carcinogens, are emitted by industrial chlorinated combustion processes and suspected to increase breast cancer risk through receptor-mediated pathways. Objectives: We estimated breast cancer risk associated with airborne dioxin exposure, using geographic information system (GIS) methods and historical exposure data. Methods: We designed a case-control study (429 breast cancer cases diagnosed between 1990 and 2008, matched to 716 controls) nested within the E3N (Etude Epidémiologique auprès de femmes de la Mutuelle Générale de l'Education Nationale) cohort. Airborne dioxin exposure was assessed using a GIS-based metric including participants' residential history, technical characteristics of 222 dioxin sources, residential proximity to dioxin sources, exposure duration and wind direction. Odds ratios (OR) and 95% confidence intervals (CI) associated with quintiles of cumulative exposure were estimated using multivariate logistic regression models. Results: We observed no increased risk of breast cancer for higher dioxin exposure levels overall and according to hormone-receptor status. We however observed a statistically significant OR for Q2 versus Q1 overall (1.612, 95% CI: 1.042–2.493) and for estrogen-receptor (ER) positive breast cancer (1.843, 95% CI: 1.033–3.292). Conclusions: Overall, as well as according to hormone-receptor status, no increased risk was observed for higher airborne dioxin exposure. The increased risk for low exposure levels might be compatible with non-monotonic dose-response relationship. Confirmation of our findings is required. Our GIS-based metric may provide an alternative in absence of ambient dioxin monitoring and may allow assessing exposure to other pollutants. Keywords: Breast cancer, Endocrine disruptors, Dioxins, Geographic information system, Tumor receptor